SECTORAL ANALYSIS ON THE IMPACT OF ISLAMIC BANKS ON THE MALAYSIAN ECONOMY - Imam Wahyudi Indrawan; Maya Puspa Rahman (Journal of Islamic Monetary Economics and Finance, 2020)
Malaysia is a well-known Islamic finance hub with a growth trend in its Islamic financial assets. The growth of the Malaysian economy since independence has also been commendable, with a rising contribution from Islamic banking and finance. This study offers a different perspective by undertaking a sectoral analysis on the impact of Islamic banks in Malaysia. It aims to fill the gap in the literature by investigating how Islamic bank financing (IBF) affects economic growth in Malaysia, both overall and at the sectoral level. Three sectors are observed in this study: agriculture, industry and services. Both long-run and short-run analyses are undertaken for the data period 2007Q1 to 2018Q4. The Autoregressive Distributed Lag (ARDL) method is utilised where IBF is found to significantly and positively affect the economic growth of Malaysia, at the overall and sectoral level. Nonetheless, there is a negative relationship in the agriculture sector and no cointegration in the industry sector. The results of this study are expected to provide insights for policymakers in encouraging more optimal Islamic financing to economic sectors in Malaysia.